If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4c + 2g)(4c + -2g) = 0 Multiply (4c + 2g) * (4c + -2g) (4c * (4c + -2g) + 2g * (4c + -2g)) = 0 ((4c * 4c + -2g * 4c) + 2g * (4c + -2g)) = 0 Reorder the terms: ((-8cg + 16c2) + 2g * (4c + -2g)) = 0 ((-8cg + 16c2) + 2g * (4c + -2g)) = 0 (-8cg + 16c2 + (4c * 2g + -2g * 2g)) = 0 (-8cg + 16c2 + (8cg + -4g2)) = 0 Reorder the terms: (-8cg + 8cg + 16c2 + -4g2) = 0 Combine like terms: -8cg + 8cg = 0 (0 + 16c2 + -4g2) = 0 (16c2 + -4g2) = 0 Solving 16c2 + -4g2 = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '4g2' to each side of the equation. 16c2 + -4g2 + 4g2 = 0 + 4g2 Combine like terms: -4g2 + 4g2 = 0 16c2 + 0 = 0 + 4g2 16c2 = 0 + 4g2 Remove the zero: 16c2 = 4g2 Divide each side by '16'. c2 = 0.25g2 Simplifying c2 = 0.25g2 Take the square root of each side: c = {-0.5g, 0.5g}
| 2x^2-8x+8=0 | | 8x+6-3x-8+2y-6y= | | 7(k-6)+8=-13 | | 0.2(500-2.3x)=3.8(3x-3000) | | 2k^2-18= | | -252=-7(x+19) | | 4x-1=2x-31 | | -44x+28y+4= | | (4w-2)(5w+4)=0 | | 18m+27=2m-3 | | -4-6x=-64 | | y-5y= | | m(m+4)(m-7)=0 | | 3(3x-1)=4(4x-1) | | 4s+8=12 | | x+11=314.86 | | -14(9+19p)=3066 | | 12(x-7)=60 | | X^2+x=2 | | 4p^2-5pq= | | 252=x+.8x | | 3(y+7)=4(y-2) | | 3m-8m=10 | | 4=p+14 | | 3x^2(4x+5)(x-6)=0 | | -6(2p+2)-24=4(3p+3) | | 4p^4-5pq= | | 1-10x=-319 | | -3p+5p+4=6 | | 6n-6=18 | | 4x^2+12x+9= | | 12n-24=-14+28 |